Sleepyhead, deadly awakening: the dynamics of metastatic organotropism, tumor dormancy and therapeutic implications - Sarkar, Soumyajit; P. K., Suresh (Frontiers in Oncology, 2025)
As per the global mortality-related data, metastasis and tumor-related relapse are the major determinants of cancer-related deaths. This phenomenon is largely driven by tumor dormancy - a state in which disseminated tumor cells (DTCs) persist in a non-proliferative phase. These dormant cells evade immune surveillance and resist conventional therapies, contributing to late relapse and metastatic outgrowth. Dormancy is maintained through intricate crosstalk between cancer cells and the microenvironment, involving extracellular matrix components, and various cellular signaling pathways. However, changes in these microenvironmental cues can disrupt this balance and reactivate dormant cells, leading to their proliferation and metastatic colonization. The undetectability of dormant DTCs complicate therapeutic targeting, underscoring the need to elucidate the molecular and epigenetic mechanisms that regulate dormancy maintenance and escape. This review explores the key signaling mechanisms and microenvironmental influences that regulates the tumor dormancy. Furthermore, we discuss emerging therapeutic strategies aimed at eradicating dormant cancer cells - either by maintaining dormant state, reactivating and sensitizing dormant cells to chemotherapy, or directly eliminating dormant populations. A deeper understanding of dormancy biology holds promise for developing innovative interventions to prevent recurrence and improve long-term patient survival.